Studying the Effect of Different Separating Medium on the Roughness of the tissue surface of Acrylic Denture Base (In Vitro Study) - Kadir, Shakhawan; hama, Niaz; hanna, Bassam (Iraqi National Journal of Nursing Specialties, 2012)
Objective: In order to evaluate the effect of different typed of Separating Medium on the roughness of the fittedtissue surface of acrylic denture base.Methodology: Chosen three types of separating medium (Group A Tin foil), (Group B Detery Isolant),(Group CCold Mould Seal),used 30 samples of hot cure acrylic resin ,10 samples for each group, after complete curing ofthese samples , Profilometer device was used to measure the surface roughness of each sample in all groups.Results: Using One Way ANOVA Test and LSD test, the results were highly significant in differences among allgroups. Although (Group A) showing lest roughness, (Group B) showing a satisfactory result of roughness, While(Group C) Showing the highest unsatisfactory surface roughness of acrylic denture base.Recommendations: make other studies on the effect of different separating medium on other properties ofthe fitted tissue surface of acrylic denture base such as hardness.